Odpowiedzi

Najlepsza Odpowiedź!
  • Kks7
  • Początkujący
2009-12-18T20:12:10+01:00
Przykład 1

3x-3y+4=8
3x-15y=5-9y

3x-3y=4 /*(-2)
3x-6y=5

-6x+6y=-8
3x-6y=5
___________________+

-3x=-3 /:(-3)
x=1

3*1-3y+4=8
x=1

-3y=8-4-3 /:(-3)
x=1

y=-1/3
x=1

Przykład 2

3(2x-1)+4(y-2)=9
2(5x-1)+3y=5(3x+y)+2

6x-3+4y-8=9
10x-2+3y=15x+5y+2

6x+4y=20
-5x-2y=4 /*(2)

6x+4y=20
-10x-4y=8
_________________+

-4x=28 /:(-4)
x=-7

6*(-7)-3+4y-8=9
x=-7

-42-3+4y-8=9
x=-7

4y=48 /:4
x=-7

y=12
x=-7

Przykład 3

4(x+2)-3(y-1)=x+y-3
3(x-4)-2(y-2)=4(x-y)+4

4x+8-3y+3=x+y-3
3x-12-2y+4=4x-4y+4

3x-4y=-3-8-3
-x+2y=4+12-4

3x-4y=-14
-x+2y=12 /*(2)

3x-4y=-14
-2x+4y=12
____________+

-x=2 /:(-1)
x=-2

3*(-2)-4y=-14
x=-2

-6-4y=-14
x=-2

-4y=-8 /:(-4)
x=-2

y=2
x=-2

Przykład 4

2(x+y)-3(x-2y)=-7x-2
5(x+1)-2(3-y)=-4(x+y)

2x+2y-3x+6y=-7x-2
5x+5-6+2y=-4x-4y

6x+8y=-2 /*6
9x+6y=1 /*(-8)

36x+48y=-12
-72x-48y=-8
_________________

-36x=4 /:(-36)
x=-1/9

6*(-1/9)+8y=-2
x=-1/9

8y=-2+2/3 /:8
x=-1/9

y=1/3
x=-1/9



1 5 1